The Structure of Urban Greening - Meliyeva Chinnigul Otakulovna; Sobitov Mireldor (Zien Journals, 2022)
This article introduces the study of urban greening, the use of landscape architecture for contemporary aesthetic and environmental purposes, and highlights the strengths and weaknesses of landscape architecture, landscape analysis, and the development of landscape theory
Keywords: Landscape system; landscape architecture; aesthetic and ecological; relief